Effect of Different Silica Compositions on Water Filter Application using the Slip Casting Method - AHMAD, SUFIZAR; NIZAM, MUHAMMAD SHAHRUL; ABDUL SHUKOR, MUHAMMAD SYAHMIE SUFI (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Water pollution problems have been a serious issue due to changes in the natural ecosystems. Researchers are working together to solve the water crisis by producing environmental-friendly water filters that are easily available in the marketplace at a low price. However, silica as the main material can pollute the environment and needs to be handled properly. The water filter process uses the casting method where it starts with the formation of a master mould according to the original water filter design. A Plaster of Paris (POP) mould is produced using a master mould. The POP mould is produced with a ratio of 75: 100 which is the weight of water and the weight of Paris powder respectively. Once the POP mould is ready, a slurry mixture consisting of water, silica and filler material will be poured into it. To produce the difference in silica composition of water filters, the slurry mixture is adjusted to 50wt%, 60wt and 70%wt. Samples of water filters are dried before undergoing a sintering process. SEM analysis results show that the sample of 70wt% silica composition had a significant pore surface. This is due to excessive water consumption which reduces the silica content. In conclusion, the different silica composition and temperature used greatly influence the rate of porosity, density and water absorption of water filtration.